Community-acquired pneumonia in the elderly - Płusa, Tadeusz (Przewodnik Lekarza/Guide for GPs, 2010)
Proper identification of community-acquired pneumonia and the decision to treat elderly patients requires knowledge of modern guidelines of management. The coexistence of other chronic pathologies in this population requires special caution and conduct therapeutic monitoring of the disease. Risk of severe complications in the form of sepsis or shock requires conducting a detailed analysis of risk factors. The proposed assessment scale community-acquired pneumonia helps classify patients in terms of risk and their eligibility for treatment in the appropriate clinical use.